Atypical burkitt's lymphoma transforming from follicular lymphoma - Chung Lap P; Loong Florence; Hwang Yu Y; Chim Chor S (BMC, 2011)
Abstract Amongst follicular lymphoma that transforms into a high-grade lymphoma, majority are diffuse large B cell lymphoma. Here we reported a rare atypical Burkitt's lymphoma transformation from an asymptomatic follicular lymphoma. Lymph node biopsy showed a composite lymphoma with infiltration of the inter-follicular areas by high grade small non-cleaved lymphoma cells amongst neoplastic follicles. Moreover, FISH and molecular genetic study confirmed concomitant MYC translocations and t(14;18) in the high-grade component, thereby suggesting the transformation of atypical Burkitt's lymphoma from an undiagnosed antecedent follicular lymphoma. The disease followed an aggressive clinical course, terminating in refractory disease 13 months after diagnosis. This is followed by a comprehensive review of the literature on lymphoma transformations from underlying follicular lymphoma after acquisition of MYC translocation, using Burkitt's lymphoma, follicular lymphoma, transformation and MYC translocations as keywords.